Application of tri-hybridized carbonaceous nanocutting fluids in an end milling operation by the minimum quantity lubrication technique. (May 2022) - Vignesh, S.; Mohammed Iqbal, U.
This paper is concentrated on the exploration of carbonaceous nanocutting fluids with the concept of tri-hybridization with improved lubricative and cooling properties by using multi-walled carbon nanotubes, hexagonal boron nitride, and graphene nanoparticles with neat cold-pressed coconut oil in a fixed volumetric proportion. The rheological properties of the nanofluids were studied to assess their performance in real-time end milling operations using an AA7075 work piece on a CNC lathe machine under a minimum quantity lubrication environment. At the outset, the carbonaceous nanofluids gave good performance when compared to conventional cutting fluids. Furthermore, the surfaces of the tribo-pairs and the chips formed were analyzed using a profilometer and high-end microscopes. The results obtained from the experiments confirm that the tri-hybridized carbonaceous nanolubricant has reduced the cutting force, tool wear, and surface roughness when correlated to monotype nanofluids. The scanning electron microscope images of the surface and tool were studied and it was found that the surface quality was maintained while end milling with tri-hybridized carbonaceous nanofluid. Improvement of ∼17%, 20% and 25% in cutting forces, surface roughness and tool wear was found in tri-hybrid fluid when compared to other fluids. Thus, the present work indicates that the addition of carbon-based nanoparticles with coconut oil has offered better performance and is found to be a credible alternative to existing conventional cutting fluids.